2001
DOI: 10.1111/1467-8624.00345
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Roles in Shaping Early Adolescents' Occupational Aspirations

Abstract: Relations among dimensions of parenting and adolescents' occupational aspirations were examined in two specific domains: academics and sports. The sample consisted of 444 seventh graders, with approximately equal numbers of African American and European American males and females, from two-parent nondivorced families. Multiple measures were used as indicators of parents' values and behaviors, youths' values and beliefs, positive identification with parents, and adolescents' occupational aspirations. In the aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
233
2
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(265 citation statements)
references
References 56 publications
21
233
2
9
Order By: Relevance
“…Jodl, Michael, Malanchuk, Eccles and Sameroff 2001;Bryant, Zvonkovic and Reynolds 2006), and parents are the family members that are most likely to influence their offspring's career choices (Schulenberg, Vondracek and Crouter 1984). Similarly, entrepreneurship research often views entrepreneurial parents as a source of entrepreneurship that fosters their offspring's entrepreneurial career intentions and behaviors (Laspita et al 2012;Lindquist, Sol and Van Praag 2015).…”
Section: Entrepreneurial Parents As a Source Of Entrepreneurshipmentioning
confidence: 99%
“…Jodl, Michael, Malanchuk, Eccles and Sameroff 2001;Bryant, Zvonkovic and Reynolds 2006), and parents are the family members that are most likely to influence their offspring's career choices (Schulenberg, Vondracek and Crouter 1984). Similarly, entrepreneurship research often views entrepreneurial parents as a source of entrepreneurship that fosters their offspring's entrepreneurial career intentions and behaviors (Laspita et al 2012;Lindquist, Sol and Van Praag 2015).…”
Section: Entrepreneurial Parents As a Source Of Entrepreneurshipmentioning
confidence: 99%
“…Although most of these intervening mechanisms are not directly captured in our regression analyses, our models of intergenerational transmission of care work are followed by models exploring whether respondents' values relevant to care are influenced by parental care work. Mothers and fathers can have enduring effects on their children's attitudes and orientations through ongoing role-modeling, application of sanctions and rewards, or transfers of knowledge and resources (Marini and Brinton 1984;Glass, Bengston, and Dunham 1986;Jodl et al 2001;Hitlin 2006;Wilhelm et al 2008). If care-working parents transmit more altruistic values, these values may in turn motivate pursuit of care work by their children.…”
Section: Parental Influences On Work Rolesmentioning
confidence: 99%
“…For example, one study showed that approximately 30% of parent-adolescent dyads did not share a single hope (Lanz et al, 2001). In general, there is considerable evidence that high parental aspirations for their children translate into high adolescent aspirations (Bandura, Barbaranelli, Caprara & Pastorelli, 2001;Behnke, Piercy & Diversi, 2004;Jodl, Michael, Malanchuk, Eccles & Sameroff, 2001;Marjoribanks, 1997Marjoribanks, , 1998Marjoribanks, , 1999Marjoribanks, , 2003bMarjoribanks, , 2003cSchoon & Parsons, 2002;Wilson & Wilson, 1992). Moreover, high parental aspirations for their children have also been found to strengthen the relationship between adolescents' aspirations and their educational achievements (Marjoribanks, 2003c).…”
Section: Processesmentioning
confidence: 99%
“…Family support is suggested to foster perceived opportunities and expectations and thus indirectly influence educational and career aspirations (Wall, Covell & Macintyre, 1999). Some studies suggest greater importance of maternal support compared to that of the father (Marjoribanks, 1993) and greater identification with the mother has been shown to be related to higher educational goals (Jodl et al, 2001). Children of mothers who encourage independence appear to score higher on goals such as leadership and independence (Budhwar et al, 2000).…”
Section: Processesmentioning
confidence: 99%